The path-dependent nature of urban governance: Emerging modes in Finland and Italy - Genova, Angela (The Greek Review of Social Research, 2016)
The socio-economic changes and the territorial reorganisation they imply (new productive districts, new emerging regional economies, etc) together with the processes of political and administrative reform bring about a deeper process of rescaling strongly affecting European urban societies since the end of the 70s. Among the main consequences we find the processes of welfare state reform towards new forms of local welfare arrangements characterised by the rhetoric of activation policies. Cities are now increasingly the main actor in the design of new welfare policies within the broader context of the reconfiguration of urban governance. The aim of the paper is to investigate the modes of urban governance emerging from the reform process common to most EU countries. My hypothesis is that there is a relationship between urban governance modes and welfare regimes. The analysis of urban welfare modes of governance in two EU capitals, Helsinki and Rome bring to light the role of local institutional milieus in shaping modes of governance. Although there are common challenges and a common response toward an increasing neoliberal role of activation policies, local institutional milieus have played a crucial role in defining a path-dependant process of reform. In social democratic welfare regimes a managerial mode of governance has emerged, stressing the central role of the State. In the familistic welfare regime, the consolidated role of third sector organizations and the non-structured and fragmented position of local public authorities in welfare policies has shaped a mode of clientelistic and corporatist governance.